ILMU SABUKU, A LOCAL TAREKAT PRACTICED FOR CENTURIES BY THE BANJAR SOCIETY, SOUTHERN KALIMANTAN - Ahmad (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2023)
Ilmu Sabuku is a spiritually nuanced Sufist from the Banjar community in southern Kalimantan, Indonesia. Ilmu Sabuku has become an integral part of religious practice, playing a role in shaping Banjar Muslim society's beliefs and way of life. Ilmu Sabuku has become a form of local Sufism that emphasises the importance of spiritual purification and achieving inner knowledge. Ilmu Sabuku teachings offer a deep understanding of the relationship between the self and the divine, as well as ways to work towards enlightenment and spiritual growth. Based on an ethnographic approach and data gathered through participant observation, in-depth interviews, and related documents, the result highlights the significant role of  Ilmu Sabuku in the religious, social, and daily life practices of the Banjar community. Even some people consider Ilmu Sabuku a "deviated" practice, but it has survived to this day. Some groups even openly keep teaching through religious meetings, through oral and written learning, as well as through visual audio, while others promote it secretly through traditional medicine and exorcism.